2015
DOI: 10.1111/dar.12285
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of behavioural interventions to reduce preoperative alcohol use

Abstract: Issues Preoperative alcohol use is associated with an increase in postoperative morbidity and mortality. Short-term abstinence prior to elective surgery has been shown to reduce postoperative risks. Therefore, behavioural intervention (BI) targeting risky drinking may have significant utility in preventing surgical complications. Approach The literature was systematically reviewed to identify the scope and outcomes of BIs aiming to reduce alcohol use in risky drinkers before they underwent surgery. Five data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 80 publications
(128 reference statements)
0
13
0
Order By: Relevance
“…Patients in the intervention group showed greater rates of smoking cessation, physical activity and weight loss than the control group and greater improvements in blood pressure. Alcohol consumption outcome data were not published in this original study report but were included in a subsequent review, 99 which identified a significant group × time interaction whereby the intervention group decreased their weekly alcohol consumption by 1.2 standard drinks per week between baseline and follow-up, whereas the control group showed an average increase of 1.3 drinks per week over the same period. With an average of > 8 months from trial entry to surgery date, patients had adequate time to implement behaviour change and observe positive health outcomes.…”
Section: Behavioural Interventions In the Preoperative Periodmentioning
confidence: 99%
See 4 more Smart Citations
“…Patients in the intervention group showed greater rates of smoking cessation, physical activity and weight loss than the control group and greater improvements in blood pressure. Alcohol consumption outcome data were not published in this original study report but were included in a subsequent review, 99 which identified a significant group × time interaction whereby the intervention group decreased their weekly alcohol consumption by 1.2 standard drinks per week between baseline and follow-up, whereas the control group showed an average increase of 1.3 drinks per week over the same period. With an average of > 8 months from trial entry to surgery date, patients had adequate time to implement behaviour change and observe positive health outcomes.…”
Section: Behavioural Interventions In the Preoperative Periodmentioning
confidence: 99%
“…A further trial considered preoperative alcohol consumption as part of a multimodal 'prehabilitation' package and planned to provide interventions for risky drinking but did not identify any patients drinking at risky levels. 102 The four studies assessing behavioural interventions for alcohol consumption in the preoperative period have been drawn together in a narrative review conducted by Fernandez et al 99 This review identified some positive findings, with two of the trials identifying significant reductions in alcohol consumption and one identifying a significant reduction in postoperative complications. However, it also highlighted a number of methodological weaknesses of the current evidence and made multiple recommendations for future research.…”
Section: Behavioural Interventions In the Preoperative Periodmentioning
confidence: 99%
See 3 more Smart Citations